Obrońca Wiary – topos hagiograficzny w Cerkwi prawosławnej - Dżega, Michał (Elpis, 2014)
In this article, the author wanted to show the specific for Orthodoxy – topos Her defender. As demonstrated by this topos is universal for any kind of holiness. Starting from the Martyrs ending the Hierarchs and Ascetics, in the Orthodox Church, there is a never-ending battle for Purity of the Faith in Christ. In this paper author have shown the three main determinants for the Fight of Faith: 1) Holy Zeal, 2) Holy Pride and 3) Holy Insubordination. To confirm his thesis the author gives some examples from the history of the Eastern Orthodox Church. At the same time author using the patristic and liturgical texts.